Discrepancy in the early childhood mortality rates obtained from the two recent surveys of Nepal - Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: In Nepal, early childhood mortality rates are derived from the Demographic and Health Surveys, which are prone to sampling and non-sampling errors being the probabilistic in nature. Thus, it is required to compare these mortality rates with other similar national survey to validate the findings. Methods: Early childhood mortality rates were calculated using one of survival analysis methods or Kaplan-Meier Life Table technique on birth histories of the 2011 Nepal Demographic Health Survey and 2011 Nepal Living Standard Survey. Life table standard errors were used to calculate confidence interval in order tostatistically compare the early childhood mortality rates within and between these surveys. Results: Life table estimates of early childhood mortalities on the 2011 Nepal Demographic Health Survey birth histories were similar to the published rates. Both surveys revealed declining trend of these mortality rates. However, estimates from 2011 Nepal Living Standard Survey were found to be significantly lower than the 2011 Nepal Demographic and Health Survey. Further, neonatal mortality was found to be stagnant during 1996-2000 and 2001-2005 periods using Living Standard Survey rather than 2001-2005 and 2006-2010 periods using Demographic and Health Survey. Conclusion: Two nationally representative surveys of Nepal carried out at same calendar year using similar survey design and identical analysis technique, gave a drastically different early childhood mortality rates.